2009
DOI: 10.1002/cbdv.200900072
|View full text |Cite
|
Sign up to set email alerts
|

Partition Coefficient and Molecular Flexibility: The Concept of Lipophilicity Space

Abstract: The rationale of this study was to investigate molecular flexibility and its influence on physicochemical properties with a view to uncovering additional information on the fuzzy concept of dynamic molecular structure. Indeed, it is now known that computed molecular interaction fields (MIFs) such as molecular electrostatic potentials (MEPs) and lipophilicity potentials (MLPs) are conformation-dependent, as are dipole moments. A database of 125 compounds was used whose conformational space was explored, while c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…VolSurf, ALMOND, MetaSite (12)). In particular, here we used VolSurf 2D descriptors, since these latter quantitatively characterize polarity and hydrophobicity, which are the main factors governing lipophilicity (13), and we already used them to calculate virtual log P N alk of molecules in the alkane/water system (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…VolSurf, ALMOND, MetaSite (12)). In particular, here we used VolSurf 2D descriptors, since these latter quantitatively characterize polarity and hydrophobicity, which are the main factors governing lipophilicity (13), and we already used them to calculate virtual log P N alk of molecules in the alkane/water system (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…As discussed in the section titled 'Property space and QSAR analyses', it should be noted that the first one is a 2D descriptor, while RMSD and variation in radius of gyration require simulations and depend on the constraining effects exerted by the simulated medium. The different nature of such flexibility descriptors is confirmed by the fair correlations between them as computed considering a large dataset of compounds (rotors vs RMSD: r 2 = 0.49; rotors vs radius variation: r 2 = 0.59; RMSD vs radius variation: r 2 = 0.44) [39].…”
Section: Molecular Properties and Their Adaptability: The Concept Of Prmentioning
confidence: 82%
“…The concept of molecular sensitivity and the discrimination between 'sensitive' and 'insensitive' (in fact, less sensitive) molecules was substantiated by considering the property space of a heterogeneous set of 125 biologically active compounds [39]. Despite what one would expect a priori, there is only a fair correlation between property ranges and molecular flexibility (as defined by the number of rotors, r 2 @ 0.5, FiguRe 5a) and this underlines that information encoded by property spaces cannot be reduced to mere structural variability.…”
Section: Graphical Representation Of the Molecular Plasticity Exprementioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, this suggests that accounting for conformational factors by considering a single (albeit optimized) conformation is not enough to take the greater informational complexity into account. Thus, a study based on a database of 125 heterogeneous compounds showed that the 3D approaches can be slightly improved by including in the predictive relationships property space descriptors that account for the dynamic profile of flexible molecules . Similarly, a recent study indicated that it is possible to derive truly accurate log P predictions for homogenous sets of molecules by combining their log P values computed by a 3D method with molecular flexibility descriptors.…”
Section: Introductionmentioning
confidence: 99%